"Sun brings all things": Sun and moon lore as biocultural knowledge on Aneityum island, Vanuatu. - K David Harrison; Neal Kelso; Dominik M Ramík; Nadine Ramík; Gregory M Plunkett; Reuben Neriam; Wina Nasauman; Wopa Nasauman; Michael J Balick (PLoS ONE)
Across the Pacific, traditional myths and contemporary narratives describe the origins, animacy, and importance to daily human activities of the Sun and Moon. In Vanuatu, Indigenous local knowledge systems interpret ways that the Sun and Moon interact with humans and plants to achieve productive and sustainable lifeways. In this ethnographic study, we explore how residents of Aneityum Island perceive and narrate the Sun and Moon's interactions with animals, humans, and plants. We consider the influence of the Sun and Moon on domains of daily life on Aneityum, including agriculture, architecture, fishing, health care, navigation, time-reckoning, and diverse ritual activities. Aneityum islanders possess generationally accumulated understandings of their relationship to the environment, framed within the local cosmology and communicated orally. Sun and Moon lore-as expressed through myths and stories-directly informs Aneityumese people's actions and efforts at sustainable living, survival technologies, and biodiversity conservation on land and sea. This body of knowledge reveals the causes and manifestations of natural phenomena, and strategies for responding to their impacts. Due to the influences of globalization, many biocultural tools that focus on Sun and Moon lore are at risk of being forgotten. The Aneityumese people-aided by outside experts-are undertaking efforts to document and revitalize this knowledge to ensure the continuity of their resilient and sustainable lifeways.